Mortality after drug-eluting stents vs. coronary artery bypass grafting for left main coronary artery disease: a meta-analysis of randomized controlled trials - Ahmad, Yousif; Howard, James P; Arnold, Ahran D; Cook, Christopher M; Prasad, Megha; Ali, Ziad A; Parikh, Manish A; Kosmidou, Ioanna; Francis, Darrel P; Moses, Jeffrey W; Leon, Martin B; Kirtane, Ajay J; et al. (European heart journal, 2020)
The optimal method of revascularization for patients with left main coronary artery disease (LMCAD) is controversial. Coronary artery bypass graft surgery (CABG) has traditionally been considered the gold standard therapy, and recent randomized trials comparing CABG with percutaneous coronary intervention (PCI) with drug-eluting stents (DES) have reported conflicting outcomes. We, therefore, performed a systematic review and updated meta-analysis comparing CABG to PCI with DES for the treatment of LMCAD. We systematically identified all randomized trials comparing PCI with DES vs. CABG in patients with LMCAD. The primary efficacy endpoint was all-cause mortality. Secondary endpoints included cardiac death, myocardial infarction (MI), stroke, and unplanned revascularization. All analyses were by intention-to-treat. There were five eligible trials in which 4612 patients were randomized. The weighted mean follow-up duration was 67.1 months. There were no significant differences between PCI and CABG for the risk of all-cause mortality [relative risk (RR) 1.03, 95% confidence interval (CI) 0.81-1.32; P = 0.779] or cardiac death (RR 1.03, 95% CI 0.79-1.34; P = 0.817). There were also no significant differences in the risk of stroke (RR 0.74, 95% CI 0.35-1.50; P = 0.400) or MI (RR 1.22, 95% CI 0.96-1.56; P = 0.110). Percutaneous coronary intervention was associated with an increased risk of unplanned revascularization (RR 1.73, 95% CI 1.49-2.02; P < 0.001). The totality of randomized clinical trial evidence demonstrated similar long-term mortality after PCI with DES compared with CABG in patients with LMCAD. Nor were there significant differences in cardiac death, stroke, or MI between PCI and CABG. Unplanned revascularization procedures were less common after CABG compared with PCI. These findings may inform clinical decision-making between cardiologists, surgeons, and patients with LMCAD.